Water-mediated phosphorylative cyclodehydrogenation: An efficient preparation of flavones and flavanones. Issue 21 (2nd November 2019) - Vimal, Manorama; Pathak, Uma; Halve, Anand Kumar
Abstract: A new synthetic strategy utilizing POCl3 -water for the conversion of 2′-hydroxychalcones to flavanones and flavones has been developed. The reagent efficiently promoted one-pot conversion of 2′-hydroxychalcones to flavones through flavanones involving cyclization and oxidative dehydrogenation. By changing the stoichiometery of the reagents, the reaction can be tuned to generate either flavanone or flavone. The developed protocol was found to be applicable for a variety of 2′-hydroxychalcones. GRAPHICAL ABSTRACT: